Brillouin Lasing with a Reduced Self-Pulsing Characteristic Using a Short-Length Erbium-Doped Fiber as the Nonlinear Gain Medium - Zarei, A.; Rosdin, R.Z.R.R.; Ali, N.M.; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Physics, 2014)
A single-wavelength Brillouin laser is demonstrated by using a 3-m-long erbium doped fiber (EDF) in a ring cavity. The EDF is used to provide both nonlinear and linear gains to generate a stimulated Brillouin scattering (SBS) and to amplify the generated SBS, respectively. The Brillouin erbium fiber laser (BEFL) operates at 1561.5 nm, where the operating wavelength is up-shifted by 0.08nm from the Brillouin pump. The operation wavelength is also tunable within 1560.6–1562.6 nm. The BEFL also shows a self-pulsing characteristic with repetition of 66.7 kHz when the BP is set around the threshold pump power of 13mW. Compared to the conventional Brillouin fiber laser with a long cavity length, the proposed BEFL exhibits a significantly lower amplitude of pulse. This laser has many potential applications, such as in optical communication and sensors.